2006
DOI: 10.1017/s148180350001397x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the SARS outbreak on visits to a community hospital emergency department

Abstract: , 18%-24%) over the 4-week study period. The greatest reduction was for combined infant and toddler visits (69%; 95% CI, 58%-79%); these did not recover the following year. However, during the SARS outbreak there was a large increase in the number of visits for respiratory illnesses in adults (61%; 95% CI, 46%-75%) and in teenagers (132%; 95% CI, 82%-182%). Conclusions: During the SARS outbreak, total ED visits fell. The relative decline was most notable for infants and toddlers. By contrast, there was an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 10 publications
(17 reference statements)
4
48
2
1
Order By: Relevance
“…One explanation for this discrepancy between our findings concerning the role of receiving information about the outbreak and those of previous studies 9,19,60,67 is that information may have a different effect on vaccine intentions depending on the stage of the outbreak. While the spread of information during the study period had no impact on likely vaccine uptake, stronger associations might have been observed earlier in the swine flu outbreak when members of the public were less certain about the transmission or nature of the illness.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…One explanation for this discrepancy between our findings concerning the role of receiving information about the outbreak and those of previous studies 9,19,60,67 is that information may have a different effect on vaccine intentions depending on the stage of the outbreak. While the spread of information during the study period had no impact on likely vaccine uptake, stronger associations might have been observed earlier in the swine flu outbreak when members of the public were less certain about the transmission or nature of the illness.…”
Section: Discussioncontrasting
confidence: 99%
“…21 Several studies have suggested that media reporting about features of an outbreak, such as the number of cases or deaths, might influence key health behaviours. 9,19,60,67 However, we found no evidence to suggest that how much people had heard about swine flu in the past week affected likely vaccine uptake or that specific aspects of what they had heard had any substantial impact. The only exception was a weak association between having heard that the number of deaths from swine flu had increased recently and greater likelihood of accepting the swine flu vaccine.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations